FAKTOR PENUNJANG DAN PENGHAMBAT USAHATANI STROBERI DI KELURAHAN RURUKAN DAN RURUKAN SATU, KECAMATAN TOMOHON TIMUR, KOTA TOMOHON - Riane W. Senewe; Agnes E. Loho; Mex L. Sondakh (AGRI-SOSIOEKONOMI, 2017)
This study aims to identify the supporting and obstacle factors of strawberry farming in the Rurukan and Rurukan Satu Villages. The study was carried out in three months, Â July to September 2016. The data used in this study were primary and secondary data. The total respondents were seven farmers consisted of 5 farmers who were still farming strawberry and two farmers who previously cultivated strawberry. The analysis used in this study was a descriptive analysis of the characteristics of the farmers and to identify the factors supporting and obstacle factors in strawberry farm. The results showed that the factors supporting the farming of strawberries were the availability strawberry seeds, the availability of organic fertilizers, natural conditions and selling prices as well as market share. While the obstacle factors in the farming of strawberries were extreme weather, land, capital, the price of fertilizer. *ael*.